Tooth Implant Supported Prosthesis Verses Implant Supported Prosthesis: A Literature Review - Biswas, B. K.; Das, B.; Saha, A.; Paul, Rahul (New Frontiers in Medicine and Medical Research Vol. 13, 2021)
Connection of a tooth to an implant by means of prosthesis has always been debatable. Aim: The aim of this review is to summarize and discuss the available information including literature review and other documentation available and our experience regarding the rigid connection between tooth and implant in fixed partial Prosthesis. Objective: We addressed clinical indications, contraindications advantages, disadvantages, and potential risks like intrusion, marginal bone loss, tooth mobility ,while fabricating teeth implant supported prosthesis and also drew few recommendations to gain and facilitate enhanced success rate with teeth implant supported prosthesis. Materials & Methods: Thirty Six (36) articles related to survival of implant supported prosthesis (ISP) and tooth implant supported prosthesis(TISP), prosthetic options like rigid connector (RC) or non rigid connector(NRC)and complications such as intrusion of teeth were selected and analyzed in order to get some outcome. Results: Although surrounded with some controversy, tooth implants supported prosthesis provides clinicians more treatment option, reduces treatment cost if used rationally. Conclusion: Connecting tooth to implant has its own benefits and risks, but it can be used a viable option in properly indicated situations.